STYLISTIC FUNCTIONS OF EPITHET - Farmanov Gayrat (PEDAGOGS, 2024)
Abstract; Epithets in English emotive prose can fulfil different stylistic functions: a descriptive function (to describe characters, views, situations, different things and feelings); an expressive function (to make the texts more expressive and emotional).